Geopolitical explanation for foreign policy of Islamic republic of Iran with an emphasis on Geo-economics capabilities - Abed Golkarami; Afshin Motaghi; Hossien Rabiee (تحقیقات کاربردی علوم جغرافیایی)
Knowing Country and understanding the capacity of its perimeter and international environment are essential components of the economy that the foreign policy of any country should be on the basis of territorial and social. The country relies on its geopolitical foundations that they are influenced by its geographical location can affect codification foreign policy in the international economy. Hence, this paper with an analytical -descriptive method to survey the geopolitical and geographical foundations of Islamic Republic of Iran's economy. This paper show that Economy of Islamic Republic Iran away with its Geopolitical foundations and to achieve an effective economic on the closed surrounding and international environment, review in Geopolitical foundations of foreign policy that is mentioned in the form of five components are necessary and is inevitable. Hence, Islamic Republic of Iran to pursue these foundations in foreign policy strategy, not only effects will be in terms of political and cultural on international environment but also in terms geo-economic impact on international political economy.